Recent Progress of DeSUMOylation in Biological Processes: A Mini Review - Wang, BS, Chiung-Min; Yang, PhD, Wei-Hsiung (North American Journal of Medicine and Science, 2012)
Post-translational modifications to proteins are essential mechanisms for controlling functions of proteins and subsequently for regulating cell fate. SUMO modification (SUMOylation) has emerged as a critical regulatory pathway in cellular function and biological processes. DeSUMOylation (removal of SUMO conjugation) by members of SUMO-specific proteases (SENPs) family makes SUMO modification highly dynamic. In this mini-review, we briefly introduce the current knowledge regarding the regulatory pathway of deSUMOylation and focus on the recent progress of functions of SENPs in biological progresses.